DSP for embedded and real-time systems expert guide - Oshana, Robert (Oxford Boston Newnes, 2012)
This book includes a range of techniques for developing digital signal processing code; tips and tricks for optimizing DSP software; and various options available for constructing DSP systems from numerous software components
Includes bibliographical references and index
Keywords: Computer software -- Development; Embedded computer systems; Signal processing -- Digital techniques